Evaluating BISMA Application Success at Jambi University Using the D&M Information Success Model - Rts Nuraini; Pradita Eko Prasetyo Utomo; Dewi Lestari (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
The BISMA application is a web-based information system adopted by Jambi University to manage the submission, review, and reporting processes for research and community service activities. As a mandatory system implemented since 2024, it is essential to evaluate its level of success and user acceptance to ensure that the system effectively supports academic and administrative needs. This study aims to assess the success of BISMA using the DeLone and McLean IS Success Model, which comprises six key constructs: System Quality, Information Quality, Service Quality, Use, User Satisfaction, and Net Benefit. This model was selected because it provides a comprehensive framework for examining system performance, information effectiveness, and the resulting impact on user satisfaction and organizational benefits. A quantitative approach was employed by distributing questionnaires to 100 respondents consisting of lecturers and internal BISMA users. The collected data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test the relationships among the model’s constructs. The findings indicate that Information Quality and User Satisfaction significantly influence system use and perceived net benefits, suggesting that accurate, relevant, and timely information plays a crucial role in enhancing the value of the system. Conversely, System Quality and Service Quality were found to have no significant effect on user satisfaction, indicating the need for improvements in system reliability, responsiveness, and technical support. Overall, BISMA is considered to provide satisfactory benefits in supporting research and community service management; however, enhancements in service quality and system stability are still required to optimize user experience and strengthen system effectiveness in the future.